2019
DOI: 10.1101/567529
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

The cellular response towards lanthanum is substrate specific and reveals a novel route for glycerol metabolism inPseudomonas putidaKT2440

Abstract: AbstractEver since the discovery of the first rare earth element (REE)-dependent enzyme, the physiological role of lanthanides has become an emerging field of research due to the potential environmental implications and biotechnological opportunities. In Pseudomonas putida KT2440, the two pyrroloquinoline quinone-dependent alcohol dehydrogenases (PQQ-ADHs) PedE and PedH are inversely produced in response to La3+-availability. This… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
2
2

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 72 publications
0
4
0
Order By: Relevance
“…It is, however, possible that additional genes/proteins required for PedH-dependent growth rely on, or are regulated by, the cytoplasmic presence of REEs. In this context, it is interesting to note that in a recent proteomic approach, we found that besides PedE and PedH, additional proteins of unknown function show differential abundance in response to La 3+ availability (Wehrmann et al, 2019). It will hence be interesting to find out, whether any of these proteins is required for PedH function.…”
Section: Discussionmentioning
confidence: 95%
See 1 more Smart Citation
“…It is, however, possible that additional genes/proteins required for PedH-dependent growth rely on, or are regulated by, the cytoplasmic presence of REEs. In this context, it is interesting to note that in a recent proteomic approach, we found that besides PedE and PedH, additional proteins of unknown function show differential abundance in response to La 3+ availability (Wehrmann et al, 2019). It will hence be interesting to find out, whether any of these proteins is required for PedH function.…”
Section: Discussionmentioning
confidence: 95%
“…We have recently reported that P. putida KT2440 is capable of using rare earth elements (REEs) of the lanthanide series (Ln 3+ ) when growing on several alcoholic substrates (Wehrmann et al, 2017, 2019). Under these conditions, the cells use the pyrroloquinoline quinone (PQQ)-dependent ethanol dehydrogenase (EDH) PedH, to catalyze their initial oxidation within the periplasm.…”
Section: Introductionmentioning
confidence: 99%
“…It is however possible that additional genes/proteins required for PedH-dependent growth rely on, or are regulated by, the cytoplasmic presence of REEs. In this context it is interesting to note that in a recent proteomic approach, we found that besides PedE and PedH, additional proteins of unknown function show differential abundance in response to La 3+ availability (Wehrmann et al, 2019). It will hence be interesting to find out in future studies whether any of these proteins is required for PedH function.…”
Section: Discussionmentioning
confidence: 98%
“…Analysis of the KT2440 genome revealed 5 further dehydrogenases that could be responsible for glycerate production in the mutant strain, these enzymes were between 2 and 2.7 fold upregulated in the transcriptomic analysis. A companion study to this work, which investigated the physiological responses of P. putida KT2440 towards rare earth elements during growth with different growth substrates, identified that two periplasmic PQQ-dependent alcohol dehydrogenases that are essential to initiate an alternative glycerol pathway via the oxidation of glycerol to glyceraldehyde (34). No significant difference in the expression of these PQQ-dependent dehydrogenases was observed in the transcriptomic analysis.…”
Section: Discussionmentioning
confidence: 99%